2016
DOI: 10.1039/c6an01159d
|View full text |Cite|
|
Sign up to set email alerts
|

In solution SERS sensing using mesoporous silica-coated gold nanorods

Abstract: Mesoporous silica-coated gold nanorods (AuNR@MS) act as a colloidally stable Raman sensing platform with a built-in analyte size cutoff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 50 publications
2
52
0
Order By: Relevance
“…Owing to the strong dependence of the SERS signals intensity on the distance to the gold surface, only the molecules smaller than the pores and able to penetrate within the silica core can chemisorb to the gold surface and will then provide a Raman signal. The absence of a Raman signal for the AuNR@SiO 2 exposed to the largest thiol of the series indicated that the molecule was unable to reach the bottom of the mesopores but rather adsorbed to their walls [ 127 ].…”
Section: Methods Of Characterizationmentioning
confidence: 99%
“…Owing to the strong dependence of the SERS signals intensity on the distance to the gold surface, only the molecules smaller than the pores and able to penetrate within the silica core can chemisorb to the gold surface and will then provide a Raman signal. The absence of a Raman signal for the AuNR@SiO 2 exposed to the largest thiol of the series indicated that the molecule was unable to reach the bottom of the mesopores but rather adsorbed to their walls [ 127 ].…”
Section: Methods Of Characterizationmentioning
confidence: 99%
“…In this case, the SERS signal intensity was dependent on the Ag satellite size and nanogap distances. Similarly, SiO 2 coated Au NPs have been employed as SERS active platforms for the detection of organic compounds, such as organic dyes, thiol compounds and biomolecules . Certain analytes might also induce the aggregation of the NPs, thus creating SERS active sites that result in high enhancement factors.…”
Section: Sers and Water Quality Analysismentioning
confidence: 99%
“…Gold nanorods (GNRs) display superior tunability in SPR absorbing through altering the length–breadth ratio and show pretty function in transforming light of NIR to heat energy; furthermore, light in NIR has maximum penetrating depth into human tissues. 17 - 21 …”
Section: Introductionmentioning
confidence: 99%